Pengembangan Kualitas Sumber Daya Manusia dalam Perspektif Ekonomi Syariah untuk Meningkatkan Daya Saing Global - Naila Nasha Najwa Yofanda; Alfina Halimatus Sa’diyah (PT. Hasba Edukasi Mandiri, 2026)
Human resource quality is one of the main determinants of a nation's competitiveness in the era of globalization and digital transformation. Along with technological advancement and increasingly complex global economic competition, human resources are expected not only to possess technical competencies but also integrity, ethics, and spiritual values. From the perspective of Islamic economics, human resource development is directed toward creating individuals who are professional, trustworthy, competent, and responsible as servants and vicegerents of Allah on earth. This study aims to analyze human resource development from the perspective of Islamic economics and its contribution to improving global competitiveness. This research employs a qualitative approach through a literature review by examining scientific journals, books, official reports, and relevant regulations published between 2020 and 2026. The findings indicate that Islamic human resource development is based on the values of amanah, ihsan, itqan, justice, and maqashid sharia, which encourage the formation of productive, innovative, and highly ethical human resources. Integrating Islamic values with digital competencies, innovation, and lifelong learning can strengthen the competitiveness of the workforce amid global economic challenges. Therefore, Islamic economics provides a comprehensive framework for developing superior human resources that are economically productive while maintaining moral and social responsibility.